Kinetic behaviour of Christia vespertilionis oil in supercritical carbon dioxide / Izni Atikah Abd Hamid - Abd Hamid, Izni Atikah (2019)
Public interest in natural drugs has enormously increased in industrialized countries with expanding use of plants and herbal medicines. Recently, one of the plant herbs involves in curing cancer diseases has emerged and is recognized as Christia vespertilionis. Previously, Christia vespertilionis was extracted using solvent extraction such as hexane, methanol and dichloromethane. Unfortunately, conventional solvent was toxic, unsafe and might contaminate the extract of the product especially product that were used for medicinal purposes. Therefore, extraction of Christia vespertilionis plant using pure supercritical carbon dioxide (SC-CO2) without any co-solvent was assessed for the first time. The aim of the research is to investigate kinetic behaviour of Christia vespertilionis oil in SC-CO2 fluid in terms of extraction yield, oil’s solubility, mass transfer and phytocompound’s characterization. The effect of extraction parameter such as temperatures (40 to 85°C) and pressures (276 to 414 bar) of SC-CO2 extraction on yield, solubility and mass transfer of Christia vespertilionis oil were evaluated. Extracted oil was then analysed under gas chromatography mass spectrometry according to their retention indices and mass spectra. Experimental data of solubility was correlated using four empirical of density-based models i.e. Chrastil (1982), del Valle and Aguilera (1988), Adachi and Lu (1983), and Sparks et al. (2008) models. Furthermore, behaviour of extraction yield and mass transfer of oil in solid and fluid phases was modeled using a Lack’s plug flow model by Sovova (1994). Results demonstrated that the oil yield and solubility were highly dependent on the extraction pressure.